Anthony Wallace and Muslim Reform Movements: A Comparative Understanding from Central and South Asia - Fouad, Shibin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This article is about a comparative understanding of Muslim reform movements in Ferghana Valley (Central Asia) and Malabar region (in the south of India, South Asia) in the context of the revitalization theory of Anthony F.C. Wallace. The historical-evolutionary approach of colonialism and the waves that it created in the ‘colonies’ show a similar trend in both regions. Both these regions witnessed a degeneration of communities, both in terms of religious and secular yardsticks. Reformation activities were initiated by individuals who attracted severe friction from society and faced alienation in different spheres of their lives. This can be depicted as a manifestation of ‘cultural lag’ in these regions. By the start of the twentieth century, international mercantile-politics took a new turn, and the globe witnessed some hitherto unheard things. When we extrapolate the graph to contemporary times, we can easily understand the repercussions these movements had produced. It helps to understand how to lead Muslim communities in other parts of the world. The methodology has been based on primary and secondary sources from libraries and online repositories. Research findings include elucidating the pattern of reform movements in geographically distinct regions at the beginning of the twentieth century and their influences on the present scenario. The novelty of this article is that the sociology of religion and reform is used in connection with historical and religious dimensions. Generally, religious reform movements are written from a religious point of view